Pengaruh Pelatihan Dan Motivasi Terhadap Kinerja Karyawan PT. Shopee International Indonesia Jakarta Selatan - Okta Zulfiah; Muhammad Akbar (JAMBIS : Jurnal Administrasi Bisnis, 2022)
This study aims to determine and analyze how much influence training and motivation have on employee performance at PT. Shopee International Indonesia, South Jakarta. In the current era of globalization, every organization or company competes with each other to show the advantages of their respective companies. Competition that continues to develop today requires companies to be able to survive in the existing competition, as well as develop every quality human resource. In every organization it can be said that one of the most important resources is human. The research method used in this research is descriptive quantitative. sample in this study, employees of PT. Shopee Department of Customer Operations Quality Assurance totaled 75 respondents with probability sampling data taken by random sampling by Taro Yamane. The types of data used in this study were obtained from primary data and secondary data. The data collection method used is a questionnaire. The data analysis technique used in this study was validity, reliability, normality test, multicollinearity test, heteroscedasticity test, multiple linear analysis, F test, T test. Research Results. Partially there is an influence between training and motivation on the performance of employees of PT. Shopee International Indonesia, South Jakarta, it is known from the results of the t-test that the results of t-count > t-table (8.33 > 1.993) then H0 is rejected and H1 is accepted. Meanwhile, according to the results of the simultaneous F test, the calculated F value is 6.503 with an F table value of 3.12. Thus, it is known that F count > F table, then together or the variables of training and motivation (simultaneously) affect the performance of employees of PT. Shopee International Indonesia, South Jakarta